Taxation and the financial structure of German outbound FDI - Jack Mintz; Alfons J. Weichenrieder (Center for Economic Studies and ifo Institute (CESifo), 2005)
The paper analyzes the financial structure of outbound FDI during the period 1996-2002 by drawing on up to 54,022 firm-year observations of 13,758 German-owned subsidiaries. We find that the tax rate in the host country has a sizeable and significantly positive effect on leverage for wholly-owned foreign unlike partially-owned foreign companies. Most of the effect comes from increased intra-company borrowing, while third-party debt is not significantly affected by tax differences. While wholly-owned subsidiaries react more sensitively to tax rate differentials, they are less sensitive to macroeconomic influences like interest rates.
Keywords: H25; F23; 330; foreign direct investment; financial structure; capital structure; taxation; Auslandsniederlassung; Kapitalstruktur; Internationale Finanzierung; Unternehmensbesteuerung; Steuerbelastung; Direktinvestition; Deutsch